Design of a multilink system for calculating high-frequency processes in electric machines with mesh windings - Chumack, Vadim; Kovalenko, Mykhailo; Tymoshchuk, Oksana; Stulishenko, Andrii; Ihnatiuk, Yevhen (Eastern-European Journal of Enterprise Technologies, 2023)
This study considers the design of a multi-link high-frequency circuit for calculating defective and defect-free insulation of mesh windings in order to increase the operational reliability of general-purpose electric machines. The object of research is mesh windings of electric machines. The problem to be solved: increasing the operational reliability of electric machines with general-purpose mesh windings by analyzing and modeling defects. The research results make it possible to model defects for the analysis of the state of insulation of electric machines with mesh windings. Special attention in the research was paid to induction motors with a worn-out resource, in particular, 4A80A4 UZ engine. The analysis includes phase-to-body capacitance, winding inductance, eddy current impedance, and winding impedance. Under the WN mode, a decrease in the impedance of the winding section from 3 % to the short-circuit mode was simulated; accordingly, the resonance frequencies for each case of 3 % were determined – 73990 Hz, short-circuit – 74450 Hz, as well as the corresponding input impedances 8938.7 and 8082.5. The corresponding voltage resonances and current resonances were also determined. Appropriate results were also given for the WG scheme. The results reported here relate to the design of the scheme and the research on the defects of the mesh winding. This contributes to the analysis of the state of insulation of mesh windings. The numerical data (resonant frequencies and input impedances) allow a better understanding of the behavior of windings in different states and degrees of defects. Given the research findings, it is possible to better identify and analyze potential defects in mesh windings, which in turn contributes to increasing the reliability of electric machines. The results of this study could be used in the field of diagnosis, service, and maintenance of electric machines with mesh windings